Subcellular Compartmentalization and Chemical Forms of Lead Participate in Lead Tolerance of Robinia pseudoacacia L. with Funneliformis mosseae - Huang, Li; Zhang, Haoqiang; Song, Yingying; Yang, Yurong; Chen, Hui; Tang, Ming (Frontiers in Plant Science, 2017)
The effect of arbuscular mycorrhizal fungus on the subcellular compartmentalization and chemical forms of lead (Pb) in Pb tolerance plants was assessed in a pot experiment in greenhouse conditions. We measured root colonization, plant growth, photosynthesis, subcellular compartmentalization and chemical forms of Pb in black locust (Robinia pseudoacacia L.) seedlings inoculated with Funneliformis mosseae isolate (BGC XJ01A) under a range of Pb treatments (0, 90, 900, and 3000 mg Pb kg–1 soil). The majority of Pb was retained in the roots of R. pseudoacacia under Pb stress, with a significantly higher retention in the inoculated seedlings. F. mosseae inoculation significantly increased the proportion of Pb in the cell wall and soluble fractions and decreased the proportionof Pb in the organelle fraction of roots, stems, and leaves, with the largest proportion of Pb segregated in the cell wall fraction. F. mosseae inoculation increased the proportion of inactive Pb (especially pectate- and protein-integrated Pb and Pb phosphate) and reduced the proportion of water-soluble Pb in the roots, stems, and leaves. The subcellular compartmentalization of Pb in different chemical forms was highly correlated with improved plant biomass, height, and photosynthesis in the inoculated seedlings. This study indicates that F. mosseae could improve Pb tolerance in R. pseudoacacia seedlings growing in Pb polluted soils.